Problem ne-identitete kot problem okoljske etike? - Justin, Martin (Analiza: časopis za kritično misel, 2025)
The Non-identity Problem as a Problem of Environmental Ethics?In environmental ethics, the non-identity problem (NIP) is often considered to be a theoretical obstacle to climate change mitigation. It is based on the conflict between the intuition that some of our actions that affect future generations have moral value and the conclusion that because of their nature of influencing identity, it is difficult to point to the people who are harmed by them. In this article, I try to show that NIP does not pose such problems. First, I present the NIP in detail. Then, I analyse two approaches that question the premise that actions such as adopting one energy policy instead of another affect the identity of future generations. The first approach calls into question the notion of identity that this premise presupposes, while the second questions the notion of influencing identity. I also highlight some possible criticisms of both approaches and respond to them. In conclusion, I consider the practical implications of NIP for environmental measures and conclude that decisions concerning future generations are, from a practical point of view, analogous to decisions concerning contemporaries.
Keywords: non-identity problem; environmental ethics; intergenerational justice; climate change